Youth’s Life Space Narrative Research - Korniienko, Inokentii O.; Barchi, Beata V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The current study aims to distinguish objects and events, which teens and adolescents include in their life’s spaces, explore differences in attitudes towards life spaces, and determine the level of life’s space satisfaction of the youth via narrative psycholinguistic research. Methods: Methodological approaches inhered in interviewing and content analysis of the texts by calculating the frequency and investigating the components of the life’s space category references that were defined based on the narrative compositions. The validity of categorisation was proved by propositional analysis. Spearman’s rank correlation method was used. Results: The research results showed that stories people tell us holds powerful sway over their memories, behaviours, and identities. The youth’s space was analysed within three content blocks: structural, interpretational, and evaluative. The structural block defined categories: people; city; habitable space; educational institution; social environment and information; activity; nature; state and patriotism; the inner world. The interpretational block analysis defined interpretational judgments and attributions of the responsibility for actions and changes in the participants’ lives. The evaluative block analysis revealed the significant differences between teenagers and adolescents and between females and males in terms of life’s space evaluation. Conclusions: The structure of teens’ and adolescents’ live space is similar, but its interpretation and evaluation are significantly different. Proceeding from teenage to adolescence is followed by such changes as growing dissatisfaction of the existing life’s space and the wish to change it; growing internality, i.e., understanding personal responsibility of the life’s space formation.